Metallic Nanoparticles for the Modulation of Tumor Microenvironment; A New Horizon - Shariatzadeh, Siavash; Moghimi, Negin; Khalafi, Farima; Shafiee, Sepehr; Mehrabi, Mohsen; Ilkhani, Saba; Tosan, Foad; Nakhaei, Pooria; Alizadeh, Ali; Varma, Rajender S.; Taheri, Mohammad (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer is one of the most critical human challenges which endangers many people’s lives every year with enormous direct and indirect costs worldwide. Unfortunately, despite many advanced treatments used in cancer clinics today, the treatments are deficiently encumbered with many side effects often encountered by clinicians while deploying general methods such as chemotherapy, radiotherapy, surgery, or a combination thereof. Due to their low clinical efficacy, numerous side effects, higher economic costs, and relatively poor acceptance by patients, researchers are striving to find better alternatives for treating this life-threatening complication. As a result, Metal nanoparticles (Metal NPs) have been developed for nearly two decades due to their important therapeutic properties. Nanoparticles are quite close in size to biological molecules and can easily penetrate into the cell, so one of the goals of nanotechnology is to mount molecules and drugs on nanoparticles and transfer them to the cell. These NPs are effective as multifunctional nanoplatforms for cancer treatment. They have an advantage over routine drugs in delivering anticancer drugs to a specific location. However, targeting cancer sites while performing anti-cancer treatment can be effective in improving the disease and reducing its complications. Among these, the usage of these nanoparticles (NPs) in photodynamic therapy and sonodynamic therapy are notable. Herein, this review is aimed at investigating the effect and appliances of Metal NPs in the modulation tumor microenvironment which bodes well for the utilization of vast and emerging nanomaterial resources.